Enhancing Autonomous Learning and Vocabulary Mastery through the Effective Utilization of Online Resources and Word Wall Activities - Dhaifi, Ilzam; Setyosari, Punaji; Widiati, Utami; Ulfa, Saida (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the substantial advantages of utilizing the Internet as a learning tool, focusing on its integration with self-directed learning strategies to enhance vocabulary acquisition. Employing a quasi-experimental approach, the research involved two groups of students subjected to different treatments. The experimental group utilized internet-based reading materials selected according to their interests, recorded key points in worksheets, and engaged in word wall activities. In contrast, the control group followed traditional vocabulary learning methods. Post-test results indicated a 15% increase in vocabulary mastery for the experimental group compared to the control group. Furthermore, students in the experimental group with higher levels of self-directed learning demonstrated superior outcomes compared to those with lower levels of self-directed learning. The study concludes that reading internet-based short stories selected according to student interests significantly enhances vocabulary acquisition. Students with high self-directed learning tendencies are more likely to explore vocabulary through these stories. Effective use of the internet stimulates student interest and improves vocabulary acquisition through word wall activities, addressing the common issue of boredom in language classrooms. This study contributes to the growing body of evidence supporting the integration of digital resources in language learning curricula, particularly in fostering student autonomy and engagement.